Why do we look at people's eyes? - Elina Birmingham; Walter F. Bischof; Alan Kingstone (Journal of Eye Movement Research)
We have previously shown that when observers are presented with complex natural scenes that contain a number of objects and people, observers look mostly at the eyes of the people. Why is this? It cannot be because eyes are merely the most salient area in a scene, as relative to other objects they are fairly inconspicuous. We hypothesized that people look at the eyes because they consider the eyes to be a rich source of information. To test this idea, we tested two groups of participants. One set of participants, called the Told Group, was informed that there would be a recognition test after they were shown the natural scenes. The second set, the Not Told Group, was not informed that there would be a subsequent recognition test. Our data showed that during the initial and test viewings, the Told Group fixated the eyes more frequently than the Not Told group, supporting the idea that the eyes are considered an informative region in social scenes. Converging evidence for this interpretation is that the Not Told Group fixated the eyes more frequently in the test session than in the study session.